2011
DOI: 10.1111/j.1600-0579.2011.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐perceived preparedness for dental practice amongst graduates of The University of Hong Kong’s integrated PBL dental curriculum

Abstract: Objectives: To determine how prepared for dental practice graduates from the integrated problem-based learning (PBL) dental undergraduate curriculum at The University of Hong Kong (HKU) perceive themselves to be and to identify factors associated with self-perceived preparedness. Materials and methods:A postal questionnaire was sent to five cohorts of dentists who had graduated from HKU's integrated PBL curriculum between 2004 and 2008. Using a 4-point Likert scale, the questionnaire assessed the self-perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 26 publications
6
69
0
5
Order By: Relevance
“…This may confirm the work of Stewart et al 16 on medical house officers suggesting increased experience would increase confidence. Ninety nine percent (n=157) of participants in the study by Yiu et al 21 Furthermore Yiu et al 21 also report that 99% (n=157) had felt prepared in placing crowns yet 28% (n=44) felt poorly prepared for multi-rooted endodontics, as is reflected in the present results (Crowns: 3.86, RCT molar: 3.25). Many other studies indicate that dental graduates in the UK have the lowest confidence in carrying out molar endodontics.…”
Section: Discussionsupporting
confidence: 60%
“…This may confirm the work of Stewart et al 16 on medical house officers suggesting increased experience would increase confidence. Ninety nine percent (n=157) of participants in the study by Yiu et al 21 Furthermore Yiu et al 21 also report that 99% (n=157) had felt prepared in placing crowns yet 28% (n=44) felt poorly prepared for multi-rooted endodontics, as is reflected in the present results (Crowns: 3.86, RCT molar: 3.25). Many other studies indicate that dental graduates in the UK have the lowest confidence in carrying out molar endodontics.…”
Section: Discussionsupporting
confidence: 60%
“…The student‐perceived knowledge on dental practice management was limited with regard to the cost of material, cost of indemnity insurance and cost of running a practice. This can be related to limited exposure of the students to dental practice management training . The familiarity with the mandatory requirement for obtaining credit points for maintaining registration with AHPRA was low (44.4%) .…”
Section: Discussionmentioning
confidence: 99%
“…(6) Hendrickson (2012) suggested that a perfect intersection for learners in the development of learning should be a student, teacher and environment with proficient educational techniques based on evidenced modalities to facilitate the end goal as the comprehensive patient treatment and optimal professional satisfaction and achievement. (7) The self-directed learning process of the individual student is initiated in response to the resources provided in a progressive environment and should adapt to the ability/experience of the student. (8) Innovative strategies to cultivate and support student learning have highlighted that educational programmes and schools should facilitate an environment that can lead to student self-directed learning and encourage professional development and patient welfare.…”
Section: Introductionmentioning
confidence: 99%
“…18,20 Accurate self-assessment is an important attribute to develop in dental students. 20 There are several studies which investigated the dental students' perceptions of their dental education, 7,9,11,13 self-perceived preparedness for general dental practice, 8,14,15 and students' evaluation of their prosthodontic curriculum. 18 The results of this study report the final year dental students' experience and self-reported confidence when performing prosthetic procedures at Yeditepe University Faculty of Dentistry.…”
Section: Discussionmentioning
confidence: 99%